STRATEGI PENGUATAN BUDAYA K3 LISTRIK SISWA VOKASI : MODEL PELATIHAN PARTISIPATIF BERBASIS PUIL 2020 DI SMKN 1 CILEUNGSI: - - Suharto, Suharto; Munir, Nur Al Anshari; Listiawati, Dwi; Yuwono, Sapto (Jurnal Pengabdian Bukit Pengharapan, 2025)
Electrical safety is a crucial aspect of electrical engineering vocational education. Basic electrical safety and health training is aimed at establishing a safe work culture starting from Vocational High Schools (SMK) with the aim of reducing workplace accidents. This Community Service (PKM) aims to improve students' safety competencies and culture through the implementation of standardized basic electrical safety and health. The main problem in partners is the gap between theoretical understanding and the low consistency of practice in the use of Personal Protective Equipment (PPE). This participatory training discusses the implementation of the community service (PKM) program at SMKN 1 Cileungsi–Bogor in December 2025, which includes the delivery of basic electrical safety and health materials, demonstrations of safe work procedures, the use of personal protective equipment (PPE), and assistance with single-phase electrical installation practices. The method used is an educational-participatory approach for 46 grade X Electrical Power Installation Engineering students, including interactive socialization, demonstrations using a trainer unit, and practical assistance. The evaluation results show a very high level of program success with an average feedback score of 4.7/5.0. The program's tangible results include the distribution of two IPR-certified books (No. 001075133 & 001075134) and a practical trainer unit to partner schools. This program has proven effective in transforming student understanding into applicable skills aligned with PUIL 2020 and the Occupational Health and Safety Law, as well as fostering more structured and safe work discipline.